Undraping the Concepts of Samhita Under the Light of Various Nyayas: A Literary Review (International Journal of Ayurveda and Pharma Research, 2023)
Nyaya deals with the theory of absolute knowledge, critical thinking, reliability of information. There are different Nyayas explain in Charaka Samhita commentary written by Chakrapani and Susruta Samhita commentary by Dalhana. Nyayas explains the complicated Shlokas and to convey the hidden truths. Materials and Methods: Texts of Charaka Samhita and Susruta Samhita along with available commentaries and published articles in journals and other material available online have been thoroughly studied. After review it was observed that Charaka Samhita has adopted a lots of Nyayas like Suchikatah nyaya, Shringagrahika nyaya, Kakadantapareeksha nyaya etc to explain the sophisticated concepts. commentators of Samhitas like Chakrapani and Dalhana have taken the help of Nyaya to express the unseen knowledge. Conclusion: For easy understandable of difficult Shlokas explain in Charak Samhita and Susruta Samhita Tikakar Chakrapani and Dalhan different Nyayas used. Here is an effort to review such Nyayas mentioned in Charaka Samhita as well as Susruta Samhita for the benefit of easy understanding of the topic, thus highlighting the unavoidable role of maxims for the better understanding of philosophical and episteomological aspects.